Paternalism with hindsight do protégés react consequentialistically to paternalism? - Mitesh Kataria; M. Vittoria Levati; Matthias Uhl (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2012)
We investigate experimentally whether the protégés' reaction to paternalism depends on the consequences of the paternalistic action to their well-being. We find that protégé punish a paternalist restricting their freedom of choice. Yet, this negative reaction is not based on principled grounds because, with hindsight, protégés punish the paternalist only if the restriction makes them worse off. Conversely, if the restriction makes them better off, the protégé on average do not punish and, sometimes, they even reward the paternalist. This suggests that protégés take a consequentialist stand on paternalism. Controlling for intentions ascribed to the patron does not alter our finding.
Keywords: C92; D6; P16; 330; paternalism; consequentialism; value of freedom; experiment; Staatliche Einflussnahme; Meritorisches Gut; Freiheit; Test